PERAN GENERASI MILENIAL DALAM PENGEMBANGAN INDUSTRI KREATIF SEBAGAI UPAYA PENANGGULANGAN KEMISKINAN DI KOTA BENGKULU - Veny Puspita; Fauzan Fauzan; Deni Triyanto (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2021)
In this paper, we propose a solution to reduce poverty in Bengkulu City through the role of the millennial generation in development of creative industry. This research uses a qualitative descriptive method that directly points to the potential of the millennial generation in developing creative industries. The data sources of this research consisted of secondary data and primary data. Secondary data were obtained from agencies or institutions, both formal and informal. While the primary data is obtained from Participatory Rural Appraisal (PRA) approach with observation data collection techniques, interviews, focus group discussions (FGD) and brainstorming. The results showed that the role of the millennial generation in developing creative industries such as product development, prices, places, promotions and resources has the potential to rapidly grow and develop as an effort to reduce poverty in Bengkulu City. This study is expected to become a reference for the government in overcoming poverty in Bengkulu City and making the creative industry a leading sector in Bengkulu City.